2018
DOI: 10.1111/jopr.12762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silane Heat Treatment by Laser on the Bond Strength of a Repair Composite to Feldspathic Porcelain

Abstract: Treatment with Er:YAG laser prior to silane application can be as effective as HF etching. Heat treatment of silane by CO or Er:YAG lasers does not improve the bond strength between feldspathic porcelain and composite resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…There are no studies available demonstrating whether Er: YAG laser irradiation modifies the surface of base metal alloys. 19 The extent of the superficial changes on the metal surface depends on the energy density of the laser radiation as well as on the type of irradiated metal.…”
Section: Discussion:-mentioning
confidence: 99%
“…There are no studies available demonstrating whether Er: YAG laser irradiation modifies the surface of base metal alloys. 19 The extent of the superficial changes on the metal surface depends on the energy density of the laser radiation as well as on the type of irradiated metal.…”
Section: Discussion:-mentioning
confidence: 99%
“…The silane bonding agent is a monomer with reactive organic radicals and a monovalent water‐soluble group that produces an adequate bond between the inorganic ceramic and the organic bonding agent phases 11 . In addition, silane increases the surface energy of the ceramic substrate and improves the wettability of the resin cement 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that heating silane can improve the bond strength results, 1,2,12–14 since it exposes deeper, reactive, and stable layers of silane. However, the literature is inconclusive regarding the most suitable technique for heating silane.…”
Section: Introductionmentioning
confidence: 99%
“…The composite-ceramic bond is dependent on the adhesion of the composite resins to the ceramic surface treatment used, and these current processes are based on micromechanical and chemical bonding [16,17]. The ceramic surfaces are prepared in a variety of ways [18], such as hydrofluoric acid etching, (HF) [16,17,[19][20][21][22][23][24][25][26][27] silica coating [19], abrasion by airborne aluminum oxide particles [28], and laser irradiation [29]. These methods are used to increase surface roughness and bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the laser technique is becoming more popular in the dentistry field. The Er:YAG laser wavelength is 2940 nm, which corresponds to the maximum of water absorption at the invisible spectrum [18,29]. Heat treatment may accelerate the silane, resulting in a long-lasting bond that strengthens the composite-ceramic link [3,5,13,19,[27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%